(untitled) - Thrusfield, Michael (London, 1986)
This book provide a comprehensive introduction to the role of epidemiology in veterinary medicine. There has been considerable expansion in the application of veterinary epidemiology: more quantitative methods are available, challenges such as the epidemic of foot-and-mouth disease in Europe in 2001 have required epidemiological investigation, and epidemiological analyses have taken on further importance with the emergence of evidence-based veterinary medicine. In this edition: Completely revised and expanded chapters; Increased attention given to the principles and concepts of epidemiology, surveillance, and diagnostic-test validation and performance; Many examples are drawn from both large and small animal medicine, and from the developing as well as the developed world . Veterinary Epidemiology is an invaluable reference source for veterinary general practitioners, government veterinarians, agricultural economists and members of other disciplines interested in animal disease. It will also be essential reading for undergraduate and intermediate-level postgraduate students of epidemiology
Keywords: Veterinary epidemiology